Robotization in modern society from the psychological point of view - Chugaeva, Nataliya (My University, 2022)
The examples of the implementation of robots with artificial intelligence in various spheres of human life and activities are given in the article. An original author's model of professional interaction between humans and robots is proposed. The author determined that for the effective implementation of robotization in modern society, the psychological qualities foreseen by world experts for 2025 must be distributed between humans and robots. In this context, the future need of society for teachers-tutors becomes clear in order to coordinate the activities of both human employees and robots. У статті наведено приклади впровадження роботів зі штучним інтелектом у різні сфери життя та діяльності людини. Запропонована оригінальна авторська модель професійної взаємодії людей та роботів. Автором визначено, що з метою ефективного впровадження роботизації в сучасному суспільстві психологічні якості, передбачені свого часу світовими експертами для 2025 р., необхідно розподілити між людьми та роботами.
Keywords: кафедра гуманітарних дисциплін; robot; robotization; artificial intelligence; professional interaction between people and robots; teacher-tutor; робот; роботизація; штучний інтелект; професійна взаємодія людей та роботів; педагог-наставник